Eating the fruit of the poisonous tree? Ecological modernisation and sustainable consumption in the EU - Anna Couturier; Kannika Thaimai (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2013)
Environmentalism has become a central concern for European Union (EU) policy makers and citizens alike as the extent of the bio-crisis has become better understood. Projects aimed at reducing the environmental costs of European living, industry, and commerce have grown in number and scope in the last twenty years. Strategies for reform have focused on the ways in which established market forces can be mobilised to create change within European systems of production and consumption. For food products, the EU has undertaken two innovative projects focused on reforming both consumers and producers: the EU Ecolabel and the EU Organic logo. Similar in design yet unique in function, these product-labelling endeavours instrumentalise the normative philosophy of ecological modernisation in the hopes that incentive-based, incremental transformation in the processes of production and consumption can adequately address the challenges of environmental degradation. We find that while some opportunities for reform of the nature of the EU food market is made possible through the EU labelling schemes, the projects have limited impact on the overall food production and consumption practices and, therefore, are not able to institute substantial and much needed ecological reform.
Keywords: 330; Ecological Modernisation; Consumer Society; Sustainable Consumption; Bio-crisis; EU Ecolabel; EU Organic logo